Perception of Undergraduate Medical Students about Integrated Modular Curriculum and Factors Affecting - Rabia Wajid, Abid Asher, Junaid Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To explore the perceptions of undergraduate medical students about integrated modular curriculum and to identify the factors affecting it. Study design: Mixed method study Place and duration of study: King Edward Medical University (KEMU) from 1st November 2021 to 30th April 2022. Methods: The questionnaires were distributed to 391 MBBS students. In depth interviews were conducted from 16 students and audio-recorded. Results: Three hundred and fifty seven (91.3%) considered integrated curriculum a useful approach, 88% preferred this approach over traditional, more than 70% considered it useful for clinical insight and improvement in academic performance. Many (43%) of the students complained that the institutional environment was not helpful regarding implementation of integrated curriculum which was further explored by in-depth interview. Conclusion: The majority of students have shown a positive response to the modular integrated curriculum .It has helped them in improving academic performance and clinical insight. There is a need to improve university environment to implement integrated assessment more effectively.